Syariah-compliance tourism in Malaysia - Abdullah, Amini Amir; Awang, Mohd Daud; Abdullah, Norsazali; Ismail, Kamarulzaman (Kolej Universiti Islam Pahang Sultan Ahmad Shah (KUIPSAS), 2022)
This study provides a detailed explanation of the definition, characteristics, concept, and principles of Syariah-compliance tourism. This is a qualitative study which explores the syariah-compliance tourism including definition, characteristics, concept, and principles based on library research and scientific conceptual approach and framework. An in-depth conceptual analysis is also applied. The findings unveiled that Syariah-compliance tourism is a new way of developing the tourism industry in Malaysia which is in line with ethics, culture, and Islamic values. Syariah-compliance tourism is not defined as the visit to the mosque alone but also nature, culture, or creativity that is integrated with Islamic values. Currently, the concept of adherence to Islam (which has been called as Shariah-compliant) has become a trend in the global economy, from food and beverage products to lifestyle and finances. As a new lifestyle trend, many countries are beginning to introduce tourism products related to the halal concept or Islamic orientation. The Islamic economic sector has grown rapidly in Malaysia and the world, including culinary, Islamic finance, Islamic takaful (insurance and mortgage) industries, fashion, cosmetics, pharmaceuticals, entertainment, and tourism.